Optimize the interactions at S4 with efficient inhibitors targeting 3C proteinase from enterovirus 71. Issue 11 (17th May 2016) - Zhang, Lanjun; Huang, Guolong; Cai, Qixu; Zhao, Chen; Tang, Liuyun; Ren, Haixia; Li, Peng; Li, Ning; Huang, Jianwei; Chen, Xueqin; Guan, Yi; You, Han; et al.
Abstract : Enterovirus 71 (EV71) is the causative agent of hand, foot and mouth disease and can spread its infections to the central nervous and other systems with severe consequences. The replication of EV71 depends on its 3C proteinase (3C pro ), a significant drug target. By X‐ray crystallography and functional assays, the interactions between inhibitors and EV71 3C pro were evaluated. It was shown that improved interactions at S4 for the substrate binding could significantly enhance the potency. A new series of potent inhibitors with high ligand efficiency was generated for developing antivirals to treat and control the EV71‐associated diseases. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : X‐ray crystallography and functional assays were employed to show that interactions at S4 of the substrate‐binding groove were important for inhibitors targeting 3C proteinase from enterovirus 71. A new series of potent inhibitors with high ligand efficiency was subsequently generated for developing antivirals to treat and control the virus infection.